Penerapan Model Pembelajaran Flipped Classroom Berbasis Guided Inquiry (FGIL) Pada Pembelajaran Kimia SMA di Kabupaten Agam Sebagai Model Untuk Pembelajaran Digital di Masa Pandemi Covid 19 - Mawardi Mawardi; Zonalia Fitriza; Okta Suryani; Suci Sukmawati; Vika Aumi (Fakultas MIPA Universitas Negeri Padang, 2021)
The occurrence of the Covid-19 Pandemic disaster that hit the world in various walks of life, especially in the world of education, one of which was at the SMA/MA level where the learning system was shifted to an online (online) or distance learning system. Basically online learning (digitizing learning) is a necessity because it is part of the characteristics of the industrial revolution 4.0 era, which must be responded to and adopted by teachers. FGIL (Flipped Guided Inquiry Learning) is an appropriate learning model used in the learning process during a pandemic, with the help of LMS. The service was carried out for 13 high school/MA chemistry teachers in Agam district. The implementation process begins with an initial analysis, then continues with implementation activities. Based on the activities that have been carried out, it can be concluded that the teacher has been able to design learning with the FGIL model assisted by the Edmodo LMS.